Analysis of the Symptoms of Split Government after the 2018 West Kalimantan Governor Election - Andi Syarif T. U. W.; Muh. Ilham; Sampara Lukman; Ella Wargadinata (International Journal of Science and Society, 2021)
This research is related to leadership, political support, and the strategy of the Governor and Deputy Governor of West Kalimantan in building political support with the DPRD in running the government in a divided government. This will be very interesting because, in the current era of government, the border area has become the front guard for the Indonesian nation in global competition. The qualitative descriptive approach was used in this study to present the evidence discovered by in-depth analysis comprehensively. This study found that electing the Governor and Deputy Governor of West Kalimantan Province would directly improve the decentralization mechanism, resulting in many positive consequences. Second, the regional head's legitimacy among the people is increasing, implying that state sovereignty in the hands of the people is genuinely realized. Third, the support and participation of the people in governance, development and social society are getting higher.